Det levende web og de døde links - Nyvang, Caroline; Kromann, Thomas Hvid; Zierau, Eld (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
The article probes web referencing behavior among Danish researchers and students. Our study is concentrated on a selection of master’s theses submitted in 2015 at the University of Copenhagen and an assortment of recent literary monographs focusing on contemporary literature. In the article we examine to what extent it is possible to follow each given web reference and we review the existing recommendations. Our study shows that current practices and ideals are inadequate, and we discuss a number of alternatives. It is our recommendation and conclusion that researchers and university students should strive to include web archives whenever they refer to internet resources. We furthermore argue that a web reference should consist of four specific elements in order to be both precise and persistent, and we introduce a concrete suggestion on how an up-to-date standard might be formulated.